2022
DOI: 10.3390/jcm11195640
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Mid-Term Outcomes of Stenting in Patients with Isolated Distal Internal Carotid Artery Stenosis or Post-Surgical Restenosis

Abstract: The aim was to evaluate the outcome of stenting in patients with isolated distal internal carotid artery (ICA) stenosis or post-surgical restenosis, as no data are currently available in the literature. Sixty-six patients (men, N = 53; median age: 66 [IQR, 61–73] years) with ≥ 50% distal ICA (re)stenosis were included in this single-center retrospective study. The narrowest part of the (re)stenosis was at least 20 mm from the bifurcation in all patients. Patients were divided into two etiological groups, ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Similar to our findings, older patients, cardiovascular diseases, smoking, obesity, and dyslipidemia have all been identified as risk factors for restenosis following CEA [ 16 , 56 , 57 ]. Furthermore, Zhou et al [ 58 ] and Hellings et al [ 59 ] demonstrated that the histopathological characteristics of carotid plaques are associated with carotid restenosis after CEA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our findings, older patients, cardiovascular diseases, smoking, obesity, and dyslipidemia have all been identified as risk factors for restenosis following CEA [ 16 , 56 , 57 ]. Furthermore, Zhou et al [ 58 ] and Hellings et al [ 59 ] demonstrated that the histopathological characteristics of carotid plaques are associated with carotid restenosis after CEA.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of risk factors (smoking, obesity, dyslipidemia), as well as the local and systemic inflammatory response are involved in post-endarterectomy restenosis [ 14 , 15 , 16 ]. Regarding the characteristics of atherosclerotic plaques, these were associated with the negative evolution of the patient with ischemic stroke [ 17 , 18 , 19 , 20 , 21 ], as well as with stent restenosis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the confirmed prevalence of the prepetrous ICA localization of atherosclerosis is low in patients > 60 years old with vascular risk factors and it is expected to be lower in young patients, even those with ischemic stroke. Another study which partially addressed the issue of distal ICA plaques and their management [ 29 ] did not consider the prepetrous segment of the ICA, as the median distance (mm) (IQR) of stenosis from the common carotid artery bifurcation is 20.4 (20.1–21.4). In our single-center series of young patients with acute ischemic stroke, 2/93 (2.15%) patients had symptomatic complicated plaques in the prepetrous ICA.…”
Section: Discussionmentioning
confidence: 99%
“…The patency rate increased to 83.3% after repeated EVT procedures for restenosis [ 28 ]. The recurrent restenosis in TAK patients outranged that seen in patients with atherosclerotic lesions [ 86 , 87 ]. On the contrary, there is a lack of clinical data on the incidence of restenosis following EVT in carotid FMD [ 88 ].…”
Section: Discussionmentioning
confidence: 99%